2011
DOI: 10.1016/j.vaccine.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Coupling sensitive in vitro and in silico techniques to assess cross-reactive CD4+ T cells against the swine-origin H1N1 influenza virus

Abstract: The outbreak of the novel swine-origin H1N1 influenza in the spring of 2009 took epidemiologists, immunologists, and vaccinologists by surprise and galvanized a massive worldwide effort to produce millions of vaccine doses to protect against this single virus strain. Of particular concern was the apparent lack of pre-existing antibody capable of eliciting cross-protective immunity against this novel virus, which fueled fears this strain would trigger a particularly far-reaching and lethal pandemic. Given that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…37 Moreover, as expected, both HCWs and HIV showed a T cell response specific for seasonal H1N1/ Brisb/07 (65.2% and 89.5%, respectively) as well as for H3N2/Brisb/07 (60.9% and 68.4%, respectively), probably due to past infections as well as to seasonal vaccination history. On the whole, no significant differences between the percentage of responding HCWs and HIV patients were found in baseline T cell response to pandemic and seasonal strains.…”
Section: Baseline Influenza Specific T Cell Response In Hcws and Haarsupporting
confidence: 73%
See 1 more Smart Citation
“…37 Moreover, as expected, both HCWs and HIV showed a T cell response specific for seasonal H1N1/ Brisb/07 (65.2% and 89.5%, respectively) as well as for H3N2/Brisb/07 (60.9% and 68.4%, respectively), probably due to past infections as well as to seasonal vaccination history. On the whole, no significant differences between the percentage of responding HCWs and HIV patients were found in baseline T cell response to pandemic and seasonal strains.…”
Section: Baseline Influenza Specific T Cell Response In Hcws and Haarsupporting
confidence: 73%
“…32,41,52 Recently, functional A/H1N1/pds/09-specific CD4 T cells were shown in donors not exposed to the pandemic virus, probably due to the high number of conserved epitopes between pandemic and seasonal H1N1 vaccine strains. 37,53 Interestingly, in the present study we showed the ability of pandemic vaccination to boost cross-reactive H1N1/Brisb/07-and H3N2/Brisb/ 07-specific T cell responses. Moreover, we found a highly significant correlation in postvaccination CMI responses between pandemic and seasonal strains, suggesting that individual responses to pandemic vaccine also influence T cell cross-reactivity against other influenza strains probably through epitope sharing mechanisms.…”
supporting
confidence: 51%
“…27 We do not presuppose that the T-cell epitopes will be sufficient; instead, it will be important to the field to determine if expanding T-cell response to cross-reactive epitopes results in a degree of cross-protection. The finding that T-cell responses to an extremely limited number (two to four) of cross-reactive epitopes may have the capacity to attenuate the course of novel H1N1-induced disease, in the absence of cross-reactive antibody response, may also lead to development of alternative approaches to "priming" immune responses and to improved means of limiting future flu pandemics, through the use of vaccines that diminish the number of individuals who develop clinical symptoms following infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we set out to identify cross-conserved T cell epitopes in the pandemic and the 2008-2009 seasonal vaccine hemagglutinin (HA) and neuraminidase (NA) antigens, as soon as the first pandemic influenza sequences became available, using immunoinformatic methods. 4 The HLA class II epitope predictions were later confirmed experimentally using peripheral blood mononuclear cells from human donors not exposed to the pandemic virus, 5 illustrating that pre-existing CD4 + T cells elicit crossreactive effector responses against the pandemic H1N1 virus. In addition, they demonstrated that the computational tools were 90% accurate in predicting CD4 + T cell epitopes and their HLA-DR-dependent response profiles in donors that were chosen at random for HLA haplotype.…”
Section: Universal H1n1 Influenza Vaccine Developmentmentioning
confidence: 93%
“…This hypothesis is supported by a number of in vitro and in vivo studies: independent studies demonstrated cytotoxic T lymphocytes (CTLs) and CD4 + T cells raised against the seasonal H1N1 viruses, A/ Brisbane/59/2007 and A/New Caledonia/20/99, respectively, were capable of responding against whole protein antigens from the pH1N1 virus. 5,[15][16][17] In mice and in humans, memory T cells to conserved epitopes have been shown to confer protection to heterotypic infection. 18,19 In addition, cross-reactive human T helper cell responses were observed for HLA-DR4 epitopes.…”
mentioning
confidence: 99%